Can More Information About Rivals' Costs Decrease Welfare?. (5th March 2015) - Brito, Duarte; Pereira, Pedro; Vareda, João
Abstract : We investigate if more information about rivals' costs increases welfare when firms compete in prices and cost‐reducing investment. When firms compete only in prices, a firm sets a higher price under partial information than under complete information if it faces an efficient rival, and a lower price otherwise. Thus, more information redistributes market share from the more efficient to the less efficient firm, with a negative impact on welfare. When firms also compete in cost‐reducing investment, more information leads a firm to decrease investment if it faces an efficient rival, and to increase investment otherwise. Welfare decreases if firms are sufficiently asymmetric and their products sufficiently differentiated.